Fungi isolated from water, feed and poultry litter of broiler chickens in the zona da mata region of the State of Alagoas, Brazil (Research, Society and Development, 2021)
Avian litter is important in the epidemiology of fungal infections, environmental quality of the sheds and in the zooeconomic performance of the birds. The objective of this study was to identify and quantify the occurrence of fungi in the water, feed and poultry litter of broilers in the region of the forest zone, state of Alagoas, Brazil. For this, collections were carried out in aviaries treated with ammonia and iodine at 4 different times. From the water and the feed, 30 mL and 30 g were collected, respectively, from the drinking fountains and bird feeders in sterile containers. In the avian litter, the samples were collected using the drag swab technique and 10g straight from the bed, resulting in 298 samples in the different analyzed sites. Subsequently, the samples were grown on Sabouraud dextrose agar plus chloramphenicol and incubated at room temperature for 7 to 15 days. Then, isolation, purification, microculture and identification of fungi were performed. Of the 298 samples evaluated, 24,221 Colony Forming Units (CFU) were obtained, 13,801 (57.0%) corresponding to filamentous fungi and 10,420 (43.0%) to yeast-like fungi. In the avian litter 18,996 (78.0%) CFU were found, among which 9,713 (40.0%) came from the litter compound and 9,283 (38.0%) resulted from the drag swab, while in the feed and water 4,152 (17.0%) and 1,076 (5%) UFC, respectively. The most common genus was Saccharomyces spp. (16.6%), followed by Fusarium spp. (12.2%) and Acremonium spp. (11.0%). These findings demonstrate the need for microbiological control measures in the sampled places, in order to ensure better conditions of well-being and health for birds and humans.